Dietary protein intake may reduce hospitalisation due to infection in Māori of advanced age: LiLACS NZ - Carol Wham; Fiona Baggett; Ruth Teh; Simon Moyes; Mere Kēpa; Martin Connolly; Santosh Jatrana; Ngaire Kerse (Elsevier, 2015)
Abstract Objective: To investigate factors related to hospital admission for infection, specifically examining nutrient intakes of Māori in advanced age (80+ years). Method: Face‐to‐face interviews with 200 Māori (85 men) to obtain demographic, social and health information. Diagnoses were validated against medical records. Detailed nutritional assessment using the 24‐hour multiple‐pass recall method was collected on two separate days. FOODfiles was used to analyse nutrient intake. National Health Index (NHI) numbers were matched to hospitalisations over a two‐year period (12 months prior and 12 months following dietary assessment). Selected International Classification of Disease (ICD) codes were used to identify admissions related to infection. Results: A total of 18% of participants were hospitalised due to infection, most commonly lower respiratory tract infection. Controlling for age, gender, NZ deprivation index, diabetes, CVD and chronic lung disease, a lower energy‐adjusted protein intake was independently associated with hospitalisation due to infection: OR (95%CI) 1.14 (1.00-1.29), p=0.046. Conclusions: Protein intake may have a protective effect on the nutrition‐related morbidity of older Māori. Improving dietary protein intake is a simple strategy for dietary modification aiming to decrease the risk of infections that lead to hospitalisation and other morbidities.